2010
DOI: 10.1525/cond.2010.090037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Suburban Habitat on A Wintering Bird Community in Coastal Northern California

Abstract: Resumen. Para evaluar los factores que influencian una comunidad suburbana de aves en la costa del norte de California, examinamos la abundancia, riqueza y diversidad de aves invernales en 75 localidades en la ciudad de Arcata. Para cada localidad utilizamos fotografías aéreas para determinar las proporciones de superficie de vegetación y zonas sin vegetación dentro de un radio de 75 m y las distancias a varios elementos del paisaje. La actividad humana fue medida y usada como una covariable en la selección de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The Ruby-Crowned Kinglet and the Golden-Crowned Kinglet are both members of the Regulidae family and tended to collide more regularly in less urbanized sites suggesting that those species are sensitive to urban development. This observation is consistent with findings by Kalinowski and Johnson (2010) who reported that the Ruby-crowned Kinglet was associated with vegetative cover and were negatively related to road and structure cover. Although trends are observable at a species and genus level, using families in a gradient analysis further helped 'GreenLevels' is the resulting data from CA Axis I and is a measure of vegetative cover summarizing canopy cover, exposed habitats, structures and building cover, road cover, and paved surfaces.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The Ruby-Crowned Kinglet and the Golden-Crowned Kinglet are both members of the Regulidae family and tended to collide more regularly in less urbanized sites suggesting that those species are sensitive to urban development. This observation is consistent with findings by Kalinowski and Johnson (2010) who reported that the Ruby-crowned Kinglet was associated with vegetative cover and were negatively related to road and structure cover. Although trends are observable at a species and genus level, using families in a gradient analysis further helped 'GreenLevels' is the resulting data from CA Axis I and is a measure of vegetative cover summarizing canopy cover, exposed habitats, structures and building cover, road cover, and paved surfaces.…”
Section: Discussionsupporting
confidence: 93%
“…The results from this direct gradient analysis suggest that distinct and predictable clusters of bird families will collide within given geographical regions that hold a set of particular environmental and building variables. Studies on bird diversity and distribution associated with landscape features have been conducted elsewhere (Melles et al 2003;Kalinowski and Johnson 2010;Minor and Urban 2010), but remain difficult to compare with a study performed in the Toronto area as some of the bird species are different or adopt different life-history strategies and as the landscape itself may differ in characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Species richness was the total number of species observed in each season, and diversity was measured using the Shannon diversity index [32]. The following species were excluded from analyses: birds flying over the site, migratory flocks, waterfowl, raptors, and species seen on <2 surveys/season [33]. Scientific names of birds documented during point counts and listed in the text are found in Table S4.…”
Section: Methodsmentioning
confidence: 99%
“…The slow conversion of natural areas and habitats to human-dominated ones drives a decrease in species richness (Emlen 1974, Walcott 1974, Beissinger and Osborne 1982, Bentley and Catterall 1997, Ford et al 2001, Melles et al 2003, Tratalos et al 2007, Kalinowski and Johnson 2010 and functional diversity (Filippi-Codaccioni et al 2009) through the loss of habitat structure and variation. Similar in result, but more specific in mechanism, homogenization predicts that as natural areas become more urban, non-native invaders will replace local, native diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The time scale of comparison allows inference on urbanization rarely possible in longitudinal studies of any kind (Tingley and Beissinger 2009), and our study is the first to examine bird-community changes in an urban green space. In addition, although an important part of avian biology, assemblages of nonbreeding birds have been studied much less than those of breeding birds (Evans et al 2009), and rarely have they been studied in a Mediterranean climate (but see Kalinowski and Johnson 2010). We used surveys in three periods, 1913-18, 1938-39, and 2006-07, to examine changes in the composition and diversity of the avian community over time.…”
mentioning
confidence: 99%